San Sebastian College-Recoletos, Cavite City : developing a strategic marketing model for long term growth - Garcia, Revelino Duquez (Animo Repository, 1988)
The study looks into the College's opportunities for future growth: (1) developing techniques for penetrating competitors' market (2) developing unsold potential market (3) developing new market potential in less related or unrelated areas and, (4) reducing costs and expenses. To provide answers posed for investigation, the study will seek to evaluate the following: (1) level of general economic activity (2) level of total industry sales (3) the College's competitive strategy (4) the counter strategies of its competitors, and (5) The College' policy toward and control over its cost structure. Of equal importance is to be able to look into its support systems. To address this need, the following prime change goals will be considered: (1) Changing the College' culture, (2) Changing the managerial strategy (3) Changing the way work is done (4) Creative adaptation to a new environment and, (5) changing communications and influence patterns. Consequently, a planned organization improvement in the following areas will be made: (1) leadership (2) organizational climate (3) satisfaction and, (4) performance. In a nut-shell, the College operates simultaneously in four different environments: (1) an economic and industry environment (2) a competitive environment (3)a internal or operating environment and, (4) an institutional environment.To maximize the College' position in all environments simultaneously, a series of multi-staged mathematical models describing the environmental factors affecting it will be developed: (1) new market potential and analysis of latent demand (2) long-term market penetration, long-term competitive objectives and long-range competitive posture (3) Strategic operations research model and, (4) general economic activity-net profits complex. The models will be tested for significance at .01 using the t - and F - tests. The identification of these environmental factors that affect the College's general economic activity and the development of their corresponding mathematical models will serve as bases in formulating policies and implications in setting up a set of objectives that will take maximum advantage of the College economic opportunities.